Identity and Political Theory - Clarissa Rile Hayward; Ron Watson (Washington University Journal of Law & Policy, 2010)
In Identity and Political Theory, Clarissa Hayward and Ron Watson intervene in this debate, theorizing an appropriate role for the state in the contested field of identity politics. They start by parsing different theories of multiculturalism that favor state recognition of minority identity, distinguished by commitments to protect identity groups from external intervention and to permit the groups to impose illiberal restrictions on their own members. They then summarize the retreat from recognition found in poststructuralist arguments that recognition promotes "particularistic attachments" and "exacerbates normalization and coercive subjectification." Their Article provides an important corrective to Charles Taylor's pathbreaking paper, The Politics of Recognition. They contend that the "recognition framework" misled the debate, failing to capture how states "play a critical role in helping produce and reproduce" identities. The question is "not whether states should intervene in identity-constitution, but how," a question they answer by urging a principle of facilitating democracy and non-domination.
Keywords: Identity politics; Political philosophy; Multiculturalism; Autonomy (Psychology); Equal protection